Loss of CNFY toxin-induced inflammation drives Yersinia pseudotuberculosis into persistency. - Wiebke Heine; Michael Beckstette; Ann Kathrin Heroven; Sophie Thiemann; Ulrike Heise; Aaron Mischa Nuss; Fabio Pisano; Till Strowig; Petra Dersch (PLoS Pathogens, 2018)
Gastrointestinal infections caused by enteric yersiniae can become persistent and complicated by relapsing enteritis and severe autoimmune disorders. To establish a persistent infection, the bacteria have to cope with hostile surroundings when they transmigrate through the intestinal epithelium and colonize underlying gut-associated lymphatic tissues. How the bacteria gain a foothold in the face of host immune responses is poorly understood. Here, we show that the CNFY toxin, which enhances translocation of the antiphagocytic Yop effectors, induces inflammatory responses. This results in extensive tissue destruction, alteration of the intestinal microbiota and bacterial clearance. Suppression of CNFY function, however, increases interferon-γ-mediated responses, comprising non-inflammatory antimicrobial activities and tolerogenesis. This process is accompanied by a preterm reprogramming of the pathogen's transcriptional response towards persistence, which gives the bacteria a fitness edge against host responses and facilitates establishment of a commensal-type life style.